Proyecto de factibilidad para la fabricación de tableros aglomerados con estopa de Coco - Flores Llugcha, Bernardo David (2022)
The purpose of this project is a feasibility study for the implementation of a coconut tow agglomerate board production plant, in the first part the justifications that prompted the launch of the project and the causes of its importance are defined, in addition a comparative table of physical and mechanical characteristics in relation to traditional wood, the applied methodology is exploratory, descriptive and inductive, next step a market study is carried out defining the demand for the chipboard through a field study carried out through surveys directed to chipboard distributors in the province of Pichincha, these results are represented in statistical tables and graphically by means of pie-type graphs, the offer is also defined, based on secondary information and data obtained by the distributors, the subtractions between the demands and offers found result in the instant demands satisfied, based on these unsatisfied demands found, an annual production of 4800 coconut tow agglomerate boards is defined, the size of the plant, said size of the plant is framed within the technical study, as well as the design of the plant, the description of the process represented in the operation and process diagram (DOP).